Ask your own question, for FREE!
Mathematics
OpenStudy (anonymous):

Solve 2(x - 4) - 6(2x - 3) = 0 A. x = -4 B. x = -1 C. x = 0 D. x = 1

OpenStudy (anonymous):

x = 1

OpenStudy (anonymous):

d

OpenStudy (vishal_kothari):

x=1

OpenStudy (anonymous):

aNSWER IS d

OpenStudy (anonymous):

THANKS

Can't find your answer? Make a FREE account and ask your own questions, OR help others and earn volunteer hours!

Join our real-time social learning platform and learn together with your friends!
Can't find your answer? Make a FREE account and ask your own questions, OR help others and earn volunteer hours!

Join our real-time social learning platform and learn together with your friends!